Protocol: An efficacy randomized controlled trial of a spelling program in primary schools. (2019) - Cockerill, Maria; Thurston, Allen; Taylor, Andy
Highlights: Protocol for an efficacy randomized controlled trial with 120 children in 10 primary schools. The intervention aims to improve spelling, writing, reading comprehension and overall literacy. The intervention is a teacher delivered programme for spelling instruction. Abstract: This paper presents the research protocol for an efficacy randomized controlled trial of a spelling program in primary schools. The program is a workforce development program that supports Teachers and Teaching Assistants develop and deliver targeted spelling instruction to children aged 8-10. The protocol outlines a research design to assess whether the program delivered over 10–12 weeks improves spelling, writing and reading-comprehension outcomes, in a sample of 120 children from 10 schools in two English districts with high socio-economic disadvantage. The outcome measures include spelling and reading standardized tests, and spelling/writing diagnostic test. A process evaluation will measure fidelity and potential for scale-up.